Flexible control of pulse intensity and repetition rate for multiphoton photostimulation - Maddalena, Laura; Ouwehand, Mariska; Safdar, Huma; Carroll, Elizabeth C. (Frontiers in Physics, 2022)
In deep tissue imaging, pulsed near-infrared lasers commonly provide high peak powers needed for nonlinear absorption, but average power and linear absorption can be limiting factors for tissue damage through heat. We implemented intra-cavity dumping within a mode-locked Ti:Sapphire laser used for two-photon computer generated holography stimulation. This system enables photostimulation in which pulse energy, average power, and repetition rate can each be varied and harnessed as degrees of freedom. We demonstrate how this system provides a new dimension of temporal control in photostimulation experiments to alter the ratio of nonlinear to linear light-tissue interactions, namely by tuning the laser repetition rate between single-shot and 3 MHz. Repetition rates below 1 MHz, yielding pulse energies over 60 nJ, facilitated holographic projections with more regions of interest than the highest repetition rate of 3 MHz. Even lower repetition rates ( 10 kHz) diminished thermal load on the sample, as characterized by quantification of heat shock protein expression in zebrafish tissue.